Effect of smoking on Polycyclic Aromatic Hydrocarbons (PAHS) concentrations in catfish and tilapia muscles - J.C. Nnaji; N.P. Ekwe (Journal of Applied Sciences and Environmental Management, 2018)
The effects of smoking on proximate composition, energy values and  concentrations of polycyclic aromatic hydrocarbons (PAHs) were studied in raw and smoked samples of catfish (Clarias gariepinus) and tilapia (Oreochromis niloticus). Crude protein was higher in the tilapia sample for both raw and smoked samples. There was significant difference (P<0.05) in the lipid contents of raw and smoked samples of both species. Mean naphthalene concentration was significantly higher (P<0.05) than those of other PAHs analyzed in raw and smoked samples of both species. Mean benzo (a) pyrene (BaP) concentrations and total mean PAH concentrations (ΣmPAH) exceeded the EU limits in raw muscle samples. All the PAHs analyzed were detected in the smoked samples. Mean BaP concentrations and total mean PAH exceeded the EU maximum limits (2.0 and 10 μg/kg) in the muscle of smoked fish and fishery products. Total mean concentration of the four indicators of PAH contamination gave the values of 0.018 and 0.050; 0.014 and 0.012 mg/kg for raw and smoked samples of catfish and tilapia respectively. It could be inferred that the smoking process generally increased the mean total PAH levels in the fish samples and there is urgent need for relevant  authorities to take appropriate action due to the public health implications of PAH contamination.